Experience in renal allograft artery embolization in the late periods after surgery before nefrotransplantatektomiey - L. S. Kokov; R. V. Storozhev; S. M. Bocharov; Yu. A. Anisimov; G. E. Belozerov; A. V. Pinchuk (Трансплантология (Москва), 2018)
The paper describes the first experience with endovascular embolization of artery of kidney graft irreversibly lost its function in fifteen years after transplantation, during preoperative preparation of patient to nefrotransplantatectomy. The purpose of the study – to show the effectiveness of the artery rentgenendovascular embolization of the artery of kidney transplant before the nefrotransplantatektomy as a method of preventing massive intraoperative bleeding and related complications. An angiography and the rentgenendovascular embolization of the artery of kidney transplant executed on the day of surgery allowed us to remove nefrotransplantat without any technical difficulties. The total intraoperative blood loss did not exceed 50 ml.